Patient‐reported versus physiologic swallowing outcomes in patients with head and neck cancer after chemoradiation. (24th December 2018) - Kirsh, Elliana; Naunheim, Matthew; Holman, Allison; Kammer, Rachel; Varvares, Mark; Goldsmith, Tessa
Abstract : Objective: The primary objective of this project was to retrospectively investigate the relationship between patient‐reported and physiologic swallowing measures after chemoradiation therapy for head neck cancer (HNC). Methods: Adult patients who underwent chemoradiation therapy for HNC and presented for videofluoroscopic swallow study were reviewed retrospectively. Surgically treated patients were excluded. Patient perception of swallowing‐related outcomes was assessed via the MD Anderson Dysphagia Inventory (MDADI) on the same day that physiologic measures of swallow function were obtained. Using vidoefluoroscopic data, the Dynamic Imaging Grade of Swallowing Toxicity (DIGEST) scale yielded measures of safety (DIGEST‐S: penetration/aspiration) and efficiency (DIGEST‐E: residue). Statistical analysis for correlation coefficients was performed. Results: Thirty patients met the inclusion criteria. The oropharynx was the most commonly affected site (70.0%), followed by the larynx (16.7%). The median radiation dose was 72 grays (Gy), and participants were assessed a mean of 4.6 (range 0–12) years following completion of treatment. There was no correlation between the MDADI and the DIGEST‐E score (Pearson rho = −0.045, P = 0.812), DIGEST‐S score (Pearson rho = 0.075, P = 0.695), or summary DIGEST grade (Pearson rho = 0.046, P = 0.810). MDADI scores did not change significantly with increasing time since radiation ( P = 0.375), whereas the DIGEST‐E scores, DIGEST‐S score, and summary DIGEST grades worsened over time ( P = 0.007, P = 0.002, and P = 0.0005, respectively). Conclusion: Assessment of swallowing physiology showed that function worsened after chemoradiation therapy, but this did not correlate with patient‐reported quality‐of‐life measures. Reduced patient awareness of swallow dysfunction years after completion of chemoradiation has implications for management of dysphagia in the face of physiologic decline. Level of Evidence: 4 Laryngoscope, 129:2059–2064, 2019